A two-phased model for library instruction. - Davis, E B (1977)
This article describes two methods of library orientation and instruction: self-paced audiotapes and computer-assisted instruction (CAI). The tapes are used to orient the user to the libraries' physical facilities, policies, services, and tools, while CAI is used to provide detailed library information in an interactive mode.